2006
DOI: 10.1007/s00402-006-0166-x
|View full text |Cite
|
Sign up to set email alerts
|

False Aneurysm of the Left Femoral Artery and Thrombosis of the Left Femoral Vein after Total Hip Arthroplasty

Abstract: We report a 75-year-old male patient with an aneurysm of the left femoral artery after cemented total hip arthroplasty. Two months after the operation, the patient showed a spherical resistance and pain in the left groin. Examination showed a big false aneurysm of the left femoral artery. After resection of the aneurysm, an endovascular stent graft vessel prosthesis was implanted. The aneurysm originated from a punctual lesion of the artery caused by a screw. Since the first description of vessel lesions in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
0
23
0
1
Order By: Relevance
“…Despite the increasing number of spine and orthopedic operations, iatrogenic arterial injuries are relatively uncommon. [1][2][3][4][5][6][7][8][9][10][11] Delay in the diagnosis and management of such injuries can result in occasional mortality and significant morbidity including limb loss. Since the first case report of arterial injury following hip arthroplasty, there have been case reports, a few case series, and one multiinstitutional study examining the incidence, predictors and management of such injuries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increasing number of spine and orthopedic operations, iatrogenic arterial injuries are relatively uncommon. [1][2][3][4][5][6][7][8][9][10][11] Delay in the diagnosis and management of such injuries can result in occasional mortality and significant morbidity including limb loss. Since the first case report of arterial injury following hip arthroplasty, there have been case reports, a few case series, and one multiinstitutional study examining the incidence, predictors and management of such injuries.…”
mentioning
confidence: 99%
“…Since the first case report of arterial injury following hip arthroplasty, there have been case reports, a few case series, and one multiinstitutional study examining the incidence, predictors and management of such injuries. [1][2][3][4][5][6][7][8][9][10][11] Previously, published reports have focused on the vascular complications of knee and hip arthroplasty and their management by open surgical techniques. [7][8][9][10][11] In this report, early and late outcome of contemporary repair of iatrogenic arterial injuries resulting from spine, upper, and lower extremity orthopedic procedures is reported.…”
mentioning
confidence: 99%
“…In addition, there was an overall 7% mortality rate and a 15% incidence of limb loss. Delayed presentation of arterial injury after THA also has been reported with false aneurysm occurrence in the femoral artery [8].…”
Section: Discussionmentioning
confidence: 97%
“…Numerous mechanisms of injury have been identified. The most common include direct trauma from retractor placement; thrombotic occlusion from atherosclerotic plaque rupture or heat polymerization, migration, or implantation of a threaded cup; acetabular protrusion with removal of the cup and/or cement; acetabular reaming; and adjunctive acetabular screw fixation [2,4,5,7,8]. Sharma et al [9] performed a questionnaire study among the members of the British Hip Society and reported on 26 vascular injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes include: a slow anastomotic leak in arterial bypass grafts [3] and dialysis access fistulae, arterial wall infections, following an overaggressive endarterectomy [4], intravenous drug abuse [5], blunt trauma [6], penetrating injury [7,8] and following traumatic fracture, fracture fixation and joint replacement surgery [9,10].…”
Section: Introductionmentioning
confidence: 99%